Estimation of current-season carbon fluxes in the rhizosphere of a tundra wetland soil - Rüggen, Norman (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2017)
Changing environmental and climate conditions require adaptation strategies from both ecosystems and the human society. The global carbon cycle is important in this context, because increasing atmospheric carbon dioxide and methane concentrations are responsible for rising atmospheric temperatures. Particularly in Arctic ecosystems, which are adapted to extreme cold, significant climate-related changes are predicted, like increased greenhouse gas emissions. Predicting greenhouse gas emissions from tundra wetland areas is an important goal for the Arctic climate change impact research, because thawing permafrost soils might show substantially increased greenhouse gas emissions. The investigation of carbon fluxes in the active layer is important, because greenhouse gas emissions (methane and carbon dioxide) originate there. For quantifying the carbon fluxes in the soil, a polygonal plant soil system was exposed to 13C-enriched CO2, which was taken up during photosynthesis. Thus, a detectable time-dependent 13C-tracer impulse in the sub-surface carbon cycle was produced, which allows measuring atmospheric-derived carbon in the soil system. For the description and quantification of carbon fluxes in the belowground, a compartment model was developed and implemented. The model was calibrated against the observed increased 13C-concentrations. This study shows that about 26 % of the carbon, which is incorporated into the system during the experimental period, was allocated into the Scorpidium-moss in the first 20 cm. In Carex-roots, the tracer was found in a depth of 36 cm, which is close to the permafrost table. The model shows that 68 % of methane is produced by CO2 - reduction. The modelled CO2 and CH4 emissions (0.274 and 0.258 mg CL-1¬¬h-1, respectively) are similar to results of other publications. Veränderte Umwelt- und Klimabedingungen zwingen viele Ökosysteme und die menschliche Gesellschaft zur Anpassung. Der globale Kohlenstoffkreislauf ist hierbei von besonderer Bedeutung, da eine Zunahme des ...